PEMBERDAYAAN PETANI MELALUI SISTEM BAGI HASIL OLEH GABUNGAN KELOMPOK TANI (GAPOKTAN) DESA SEGOBANG KECAMATAN LICIN KABUPATEN BANYUWANGI - Ahmad Khoirin Andi (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2019)
Economy is the basic foundation in creating community welfare. Banking efforts and creativity are carried out in order to contribute to the improvement of the community's economy. One of them is islamic banking. These two decades of banking that are in indonesia offer a different concept than conventional banking that was first there. The most popular concept is the mudhorobah contract. One of the agreements deemed very beneficial especially among these farmers, has contributed to helping the economy, especially for farmers.